2013
DOI: 10.1016/j.celrep.2013.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The Human Protein PRR14 Tethers Heterochromatin to the Nuclear Lamina during Interphase and Mitotic Exit

Abstract: SUMMARY The nuclear lamina is a protein meshwork that lies under the inner nuclear membrane of metazoan cells. One function of the nuclear lamina is to organize heterochromatin at the inner nuclear periphery. However, very little is known about how heterochromatin attaches to the nuclear lamina and how such attachments are restored at mitotic exit. Here we show that a previously unstudied human protein, PRR14, functions to tether heterochromatin to the nuclear periphery during interphase, through associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
174
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(196 citation statements)
references
References 46 publications
19
174
3
Order By: Relevance
“…We demonstrated that PRR14 functions to tether heterochromatin to nuclear lamina, thus maintaining the peripheral nuclear heterochromatin compartment. Also, we showed that PRR14 may play a role in mitotic specification of H3K9me3-marked heterochromatin positioning at the nuclear lamina 56 , 59 …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We demonstrated that PRR14 functions to tether heterochromatin to nuclear lamina, thus maintaining the peripheral nuclear heterochromatin compartment. Also, we showed that PRR14 may play a role in mitotic specification of H3K9me3-marked heterochromatin positioning at the nuclear lamina 56 , 59 …”
Section: Discussionmentioning
confidence: 73%
“…We have investigated in detail the function of the factor, PRR14 56 . It was shown recently that the nuclear lamina plays an important role in maintaining an epigenetically silent heterochromatin compartment at the nuclear periphery 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have focused on identifying proteins that tether chromatin to the lamina (Gonzalez-Sandoval et al, 2015; Poleshko et al, 2013; Solovei et al, 2013) as well as defining the critical epigenetic histone modifications and enzymes involved in regulation of nuclear architecture (Gonzalez-Sandoval et al, 2015; Guelen et al, 2008; Harr et al, 2015; Kind et al, 2015; Kind et al, 2013; Therizols et al, 2014; Towbin et al, 2012). One such factor is Hdac3, a histone deacetylase (HDAC) that interacts at the inner nuclear membrane with multiple proteins, including Lamina-associated polypeptide 2 (Lap2β; Somech et al, 2005; Zullo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In most cells, at least one class of heterochromatin is positioned at the nuclear lamina, resulting in gene repression (Andrulis et al, 1998;Finlan et al, 2008;Guelen et al, 2008;Kumaran and Spector, 2008;Peric-Hupkes et al, 2010;Reddy et al, 2008;Solovei et al, 2013;Towbin et al, 2012). Previous studies also propose that heterochromatin relocation to the nuclear lamina might occur via active tethering mediated by discrete molecular complexes (Chubb et al, 2002;Poleshko et al, 2013). These perinuclear heterochromatin hotspots are enriched with histone 3 lysine 9 dimethylation (H3K9me2) and trimethylation (H3K9me3) modifications, which are usually associated with a number of heterochromatin binding proteins such as KRAB-associated protein 1 (KAP1/TIF1b/TRIM28), a binding partner of histonelysine N-methyltransferase SETDB1 (Grewal and Jia, 2007;Nielsen et al, 1999;Ryan et al, 1999;Zeng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%